Clinical significance of serum human epididymis protein 4 in liver fibrosis: An experimental study. Issue 48 (25th November 2020) - Hou, Yulei; Li, Fengzeng; Chen, Juanjuan; Zhao, Jinqiu; Li, Detao; Chen, Hui
Abstract: Background: Human epididymis protein 4 (HE4) has been identified as marker for renal fibrosis. Present study aimed to investigate the clinical significance of serum HE4 in liver fibrosis. Methods: Serum from 65 liver fibrosis patients, 68 hepatic patients without fibrosis, and 50 controls was collected respectively. Serum HE4 levels were measured by chemiluminescence immunoassay and compared among the groups. The relationships between serum HE4 levels and the clinical characteristics of liver fibrosis were also analyzed. A receiver operator characteristic curve was plotted to investigate the diagnostic efficacy of serum HE4 for liver fibrosis. Child–Pugh (C–P) score and liver fibrosis score were also evaluated. Data were analyzed by statistical software 13.0. Results: Serum HE4 levels were significantly higher in liver fibrosis than that of controls [105.35 (82.64, 164.18) vs 46.2 (39.9, 58.9) pmol L −1, P = .00] and hepatic patients without liver fibrosis [105.35 (82.64, 164.18) vs 51.00 (44.02, 65.65) pmol L −1, P < .01]; Serum HE4 levels in liver fibrosis patients with C–P class C were significantly higher than those with C–P class A [143.75 (106.50, 186.08) vs 81.42 (69.73, 99.26) pmol L −1, P = .005] and C–P class B [143.75 (106.50, 186.08) vs 113.10 (88.92, 169.50) pmol L −1, P = .01]; the diagnostic sensitivity and specificity of serum HE4 levels for liver fibrosis detection were 87.5% and 81.1%, at a cutoff value of 69 pmol L −1 ; Serum HE4 levels in alcoholic liver fibrosis were higher than that of liver fibrosis with hepatitis B virus infection [131.30 (100.67, 228.35) vs 89.46 (73.74, 116.45) pmol L −1, P < .01]. Conclusion: Serum HE4 was closely correlated with C–P class and might be a potential marker for liver fibrosis.